2023
DOI: 10.3389/fenvs.2022.1078357
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal heterogeneity effect of technological progress and agricultural centrality on agricultural carbon emissions in China

Abstract: Reducing agricultural carbon emissions is an important aspect of achieving China’s carbon peak and neutrality goals. Different agricultural centrality result in different agriculture status and role in different regions, affecting agricultural carbon emissions. In this study, agricultural centrality is introduced from the perspective of social network analysis. Spatial autocorrelation analysis, geographically and temporally weighted regression (GTWR) and other methods are used to empirically explore the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A smaller agricultural carbon emissions value represents a higher level of agricultural green development. The carbon emissions from agriculture are examined based on a broad agricultural scope, reflecting the level of agricultural green development [57][58][59][60][61][62][63][64].…”
Section: Research On the Measurement Of Agricultural Green Developmen...mentioning
confidence: 99%
“…A smaller agricultural carbon emissions value represents a higher level of agricultural green development. The carbon emissions from agriculture are examined based on a broad agricultural scope, reflecting the level of agricultural green development [57][58][59][60][61][62][63][64].…”
Section: Research On the Measurement Of Agricultural Green Developmen...mentioning
confidence: 99%
“…In the study of the spatial correlation network structure of technological progress, Wang et al concluded that there are obvious spatial correlation and spillover effects in the development of agricultural science and technology innovation in China and presented the shape of the spatial correlation network structure [28]. He et al concluded that agricultural location centrality and intermediary centrality have a significant positive moderating effect on technological progress [29].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Meanwhile, with the development of the regional economic level, environmental regulations significantly affect total factor productivity in agriculture and show a positive correlation [20,21]. Some academics believe that significant differences exist in economic development, technological progress, population, and other factors across China owing to its vast size [22][23][24][25], which, in turn, also leads to significant spatial heterogeneity in the impact of various factors on carbon emissions [26][27][28].…”
Section: Introductionmentioning
confidence: 99%